Public Goods and Ethnic Divisions - Alesina, A.; Baqir, R.; Easterly, W. (Quarterly Journal of Economics, 1999)
We present a model that links heterogeneity of preferences across ethnic groups in a city to the amount and type of public goods the city supplies. We test the implications of the model with three related data sets: U. S. cities, U. S. metropolitan areas, and U. S. urban counties. Results show that the shares of spending on productive public goods—education, roads, sewers and trash pickup—in U. S. cities (metro areas/urban counties) are inversely related to the city's (metro area's/county's) ethnic fragmentation, even after controlling for other socioeconomic and demographic determinants. We conclude that ethnic conflict is an important determinant of local public finances.